Photothermal Desorption of Toluene from Carbonaceous Substrates Using Light Flash - Floyd, Evan L. (2022)
Millions of workers are occupationally exposed to volatile organic compounds (VOCs) annually. Current exposure assessment techniques primarily utilize sorbent based preconcentrators to collect VOCs, with analysis performed using chemical or thermal desorption. Chemical desorption typically analyzes 1 µL out of a 1 mL (0.1%) extraction volume providing limited sensitivity. Thermal desorption typically analyzes 100% of the sample which provides maximal sensitivity, but does not allow repeat analysis of the sample and often has greater sensitivity than is needed. In this study we describe a novel photothermal desorption (PTD) technique to bridge the sensitivity gap between chemical desorption and thermal desorption. We used PTD to partially desorb toluene from three carbonaceous substrates; activated carbon powder (AC-p), single-walled carbon nanotube (SWNT) powder (SWNT-p) and SWNT felts (SWNT-f). Sorbents were loaded with 435 ug toluene vapour and irradiated at four light energies. Desorption ranged from <0.007% to 0.86% with a single flash depending on substrate and flash energy. PTD was significantly greater and more consistent in SWNT-f substrates compared to AC-p or SWNT-p at all irradiation energies. We attribute the better performance of SWNT-f to greater utilization of its unique nanomaterials properties: high thermal conductivity along the nanotube axis, and greater interconnection within the felt matrix compared to the powdered form.